2021
DOI: 10.1002/tsm2.269
|View full text |Cite
|
Sign up to set email alerts
|

The association between vitamin D status and overuse sport injuries: A systematic review and meta‐analysis

Abstract: Overuse injuries in sports are common and include stress fracture and musculoskeletal inflammation. Vitamin D is important in bone metabolism and exerts anti‐inflammatory effects, and it may be protective against those injuries. The objective was to evaluate the association between vitamin D status and sport injuries. This systematic review was conducted according to the PRISMA statement. We used systematic literature search in PubMed, Embase, Cochrane and Sportdiscus until the 28th of June 2020. We included o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In addition, a recent systematic review and meta-analysis of RCTs in postmenopausal women has summarised the effects of vitamin D supplementation (with or without calcium) on measures of muscle strength and mobility. The study suggests that vitamin D supplementation does not affect mobility, though there was a minor improvement in muscle strength after (84).…”
Section: Vitamin D and Musculoskeletal Healthmentioning
confidence: 72%
See 1 more Smart Citation
“…In addition, a recent systematic review and meta-analysis of RCTs in postmenopausal women has summarised the effects of vitamin D supplementation (with or without calcium) on measures of muscle strength and mobility. The study suggests that vitamin D supplementation does not affect mobility, though there was a minor improvement in muscle strength after (84).…”
Section: Vitamin D and Musculoskeletal Healthmentioning
confidence: 72%
“…Only two studies reported that low serum vitamin D concentrations were associated with musculoskeletal injuries. A heterogeneous definition and reporting of musculoskeletal injuries may have influenced the results ( 84 ).…”
Section: Vitamin D and Musculoskeletal Healthmentioning
confidence: 99%
“…Mayo Clinic Laboratories assessed 25(OH)D using gold standard LC-MS/MS methodology. An “optimization” cut point was established at 30 ng/mL (75 nmol/L) based on prior literature indicating optimal health outcomes at this concentration [11, 13, 15, 28]. ELISA was used to assess 1,25-dihydroxy vitamin D (1,25(OH) 2 D; Biovendor R&D RIS024R and RIS021R), free 25(OH)D (Biovendor R&D KAPF1991) and vitamin D binding protein (DBP; R&D Systems DY008B and DY3778B-05) according to the manufacturer’s instructions.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Mayo Clinic Laboratories assessed 25(OH)D using gold standard LC-MS/MS methodology. An "optimization" cut point was established at 30 ng/mL (75 nmol/L) based on prior literature indicating optimal health outcomes at this concentration [11,13,15,28]. ELISA was used to assess 1,25-dihydroxy vitamin D…”
Section: Circulating Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation